Hybrid fuzzy evaluation algorithm for power system protection security assessment - Meyer, Georg Janick; Lorz, Tobias; Wehner, Rene; Jäger, Johann; Dauer, Maximilian; Krebs, Rainer (Electric Power Systems Research, 2020)
System Protection Security Assessment is an important task in modern energy grids to ensure system security at all. The assessment system is particularly challenged by multivariate grid structures caused by volatile renewable infeeds. This paper presents an innovative strategy to evaluate the protection relay coordination of system-wide power grids. A way to calculate the quality of all protection relays based on realistic simulation data and independent of the protection method was sought. The hybrid algorithm consists of two major steps. First, a systematic analysis with various fault simulations is performed and the measurement results of all relays of all simulations are used as database. Subsequently, the use of fuzzy sets allows to express the quality of each relay setting regardless of its type. Specifically developed for the use of an optimization algorithm, finally, a new protection coordination is determined for an adapted version of the IEEE 9 bus grid. The results are validated, discussed and the effectiveness of the methodology compared to conventional setting rules.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Fuzzy evaluation; Optimization algorithm; Protection coordination; Protection security assessment; Relay settings